The Relationship Between Learning Approaches and Learning Motivation For Program Paket C at Suka Maju Sejahtera Community Learning Center (PKBM) in Padang City - Wahyu Budiman; Irmawita Irmawita (Universitas Negeri Padang, 2020)
This research was motivated by the low learning motivation of the citizens of learning package C at PKBM Suka Maju Sejahtera, Padang City. The low learning motivation of the learning citizens is thought to be due to the lack of this approach, presumably due to the lack of approach given by the tutor to the learning community at the time of learning. The purpose of this research is to describe the learning approach of the Program Paket C in PKBM Suka Maju Sejahtera, to describe the learning motivation of the learning citizens of the Program Paket C at PKBM Suka Maju Sejahtera, and to examine the relationship between the two. This research uses quantitative research with correlational descriptive method. The population in this study amounted to 89 citizens who participated in the Program Paket C for IPA and Social Studies classes at PKBM Suka Maju Sejahtera, Padang City with a sample of 45 people. The data collection technique used in this study was a questionnaire, with data analysis using the percentage formula and the product moment. The results of this study indicate that: (1) The learning approach applied by the tutor in the Program Paket C at PKMB Suka Maju Sejahtera Padang City is still not right; (2) The learning motivation of the citizens to learn in the Program Paket C in PKMB Suka Maju Sejahtera, Padang City is still low; (3) there is a relationship between the learning approach and the learning motivation of learning citizens in the Program Paket C at PKMB Suka Maju Sejahtera, Padang City.Keywords: learning approach, learning motivation